1998
DOI: 10.1111/j.1745-4530.1998.tb00439.x
|View full text |Cite
|
Sign up to set email alerts
|

The Response of Some Properties of Fruits to Vacuum Impregnation

Abstract: The behavior of several fruits (three varieties of apples, strawberry, kiwi‐fruit, mango and peach) during vacuum impregnation (VI) treatments was studied by using specially designed equipment and methodology to determine deformation and impregnation levels in fruit samples. The coupling of the Hydrodynamic Mechanism (HDM) and the Deformation‐Relaxation Phenomena (DRP) was analyzed throughout the two typical steps of VI process (first period at vacuum pressure and second period at atmospheric pressure). VI exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
68
0
18

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(100 citation statements)
references
References 6 publications
14
68
0
18
Order By: Relevance
“…As mentioned previously, Salvatori et al (1998) reported that in plant tissue samples of about 2 cm in characteristic dimension, with the relatively large intercellular spaces and elastic cellular arrangement, the necessary lengths of vacuum time and restoration time are within 5 min. Nevertheless, in big pieces with small pores, much more time could be necessary to complete sample equilibration in mechanical terms because of difficulties for gas release.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…As mentioned previously, Salvatori et al (1998) reported that in plant tissue samples of about 2 cm in characteristic dimension, with the relatively large intercellular spaces and elastic cellular arrangement, the necessary lengths of vacuum time and restoration time are within 5 min. Nevertheless, in big pieces with small pores, much more time could be necessary to complete sample equilibration in mechanical terms because of difficulties for gas release.…”
Section: Resultsmentioning
confidence: 89%
“…Gras et al (2003) used a vacuum pressure of 5 kPa for 10 min, and a 10-min restoration time for impregnation of isotonic solutions of sucrose and calcium lactate mixtures for eggplants, carrots and oyster mushroom. Salvatori et al (1998) reported that in plant tissue samples of about 2 cm in diameter, with relatively large intercellular spaces and elastic cellular arrangement, the necessary length of vacuum period in VI operations is on the order of 5 min and impregnation times with sugar syrups are on the order of the time required to achieve a stationary pressure in the tank after the valve is opened to restore atmospheric pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, porous materials are suitable for VI (Salvatori et al, 1998). On the other hand, FI can be applied to various kinds of materials regardless of its porosity.…”
Section: Effects Of Freezing Time On Volume Expansion and Enzyme Imprmentioning
confidence: 99%
“…The flow of water and soluble solid during the vacuum impregnation implies changes in structural and transport properties (CHIRALT; FITO, 2003). The structural changes in the tissue depend on the distance in relation to the sample surface in contact with the infusion solution, according to profiles developed from the concentration (SALVATORI; ANDRÉS; CHIRALT, 1998). The thickness of the fruit in contact with the solution determines a good impregnation, because larger and thicker fruits hinder the solute entrance.…”
Section: Loss Of Cellular Fluid (Lcf)mentioning
confidence: 99%